Understanding the Complexity of Teacher Emotions From Online Forums: A Computational Text Analysis Approach - Chen, Zixi; Shi, Xiaolin; Zhang, Wenwen; Qu, Liaojian (Frontiers in Psychology, 2020)
Teacher emotions are complex as emotions are unique to individuals, situated within specific contexts, and vary over time. This study contributed in synthesizing theories of the complexity in two characteristics of multi-dimensionality and dynamics. Further, we provided large-scale empirical evidence by employing big data and computational text analysis. The data contained around one million teachers’ online posts from 2007 to 2018. It was scraped from three representative forums of teachers’ workplace events and personal life occasions in a popular American teacher website. By conducting thread-level sentiment analysis in forums, we computed word-frequency based eight discrete emotions ratios (i.e., anger, anticipation, disgust, fear, joy, sadness, and trust) and the degrees of sentiment polarity (i.e., positive, negative, and neutral). We then used latent Dirichlet allocation for topic classifications. These topics, proxies of contexts, covered a holistic range of teachers’ real-life events. Some topics are in the main interest of scholars, such as teachers’ professional development and students’ behavioral management. This paper is also the first to include the less scholarly studied contexts like professional dressing advice and holiday choices. Then we examined and visualized variations of emotions and sentiments across 30 topics along with three scales of time (i.e., calendar year, calendar month, and academic semesters). The results showed that teachers tended to have positive sentiments in the online professional community across the past decade, but all eight discrete emotions presented. The compositions of the specific emotion types varied across topics and time. Regarding the topics of students’ behavior issues, teachers’ negative emotions’ ratios were higher compared with it was presented in other topics. Their negative emotions also peaked during semesters. The forum of teachers’ personal lives had positive emotions pronounced across topics and peaked during the wintertime. This paper summarized the evidenced multi-dimensionality characteristic as the multiple types of emotions as compositions and varying degrees of sentiment polarity of teachers. The dynamics characteristic is that teachers’ emotions vary across contexts from their workplace to personal lives and over time. These two characteristics of complexity also suggested potential interplay effects among emotions and across contexts over time.